A comment on the multifaceted relationship between multinational enterprises and within-country inequality. Issue 1 (13th May 2020) - Narula, Rajneesh; van der Straaten, Khadija
Abstract : Purpose: Whether by direct or indirect action (or by inaction), multinational enterprises (MNEs) can have both a positive and a negative effect on within-country social and economic inequality. This paper aims to comment on this multifaceted relationship between MNEs and within-country inequality. Design/methodology/approach: Given the absence of either robust theory or evidence in the neglected realm of MNEs and within-countries inequalities, this paper offers some general observations, highlights some of the key issues and illustrates possible avenues for future research studies. Findings: The capacity of MNEs to upgrade economic activity in the host country is a key policy objective. MNEs have arguably contributed to reducing income inequalities between countries. However, the limited evidence available suggests that the gains of FDI are rarely evenly distributed within recipient countries, and many of the underlying dynamics need further investigation. Social implications: The authors broaden the engagement with inequality beyond income levels, as this is just one aspect of inequality that shapes or impedes human development. They believe it is necessary – for both MNEs and policymakers – to have a more nuanced understanding of how, and under what circumstances, the presence of MNEs affects inequality in host economies. Originality/value: This paper relates the large literature on inequality (going beyond the mainstream focus on income inequality) to the mainstream understanding of MNE-assisted development.